Back Cover: Understanding the Origins of Nucleophilic Hydride Reactivity of a Sodium Hydride–Iodide Composite (Chem. Eur. J. 21/2016). Issue 21 (18th April 2016) - Hong, Zonghan; Ong, Derek Yiren; Muduli, Subas Kumar; Too, Pei Chui; Chan, Guo Hao; Tnay, Ya Lin; Chiba, Shunsuke; Nishiyama, Yusuke; Hirao, Hajime; Soo, Han Sen
Abstract : NaH, as taught in organic chemistry textbooks, is typically unsuitable as a hydridic reagent. Like the space shuttle trapped in the cage of our molecular model, NaH is unable to escape the strong ionic lattice. With the help of the NaI booster, NaH forms a novel composite that can overcome a lower energy barrier. This work explains our breakthrough in using NaH as a nucleophilic hydride and—akin to the space shuttle—boldly going where no chemist has gone before. More information can be found in the Full Paper by S. Chiba, Y. Nishiyama, H. Hirao, H. S. Soo et al. onpage 7108 ff.